Open notes sounds great, but will a provider's documentation change? An exploratory study of the effect of open notes on oncology documentation. Issue 3 (17th August 2021) - Rahimian, Maryam; Warner, Jeremy L; Salmi, Liz; Rosenbloom, S Trent; Davis, Roger B; Joyce, Robin M
Abstract: Objective: The effects of shared clinical notes on patients, care partners, and clinicians ("open notes") were first studied as a demonstration project in 2010. Since then, multiple studies have shown clinicians agree shared progress notes are beneficial to patients, and patients and care partners report benefits from reading notes. To determine if implementing open notes at a hematology/oncology practice changed providers' documentation style, we assessed the length and readability of clinicians' notes before and after open notes implementation at an academic medical center in Boston, MA, USA. Materials and Methods: We analyzed 143 888 notes from 60 hematology/oncology clinicians before and after the open notes debut at Beth Israel Deaconess Medical Center, from January 1, 2012 to September 1, 2016. We measured the providers' (medical doctor/nurse practitioner) documentation styles by analyzing character length, the number of addenda, note entry mode (dictated vs typed), and note readability. Measurements used 5 different readability formulas and were assessed on notes written before and after the introduction of open notes on November 25, 2013. Results: After the introduction of open notes, the mean length of progress notes increased from 6174 characters to 6648 characters ( P < .001), and the mean character length of the "assessment and plan" (A&P) increased from 1435 characters to 1597 characters ( P < .001). The Average Grade Level Readability of progress notes decreased from 11.50 to 11.33, and overall readability improved by 0.17 ( P = .01). There were no statistically significant changes in the length or readability of "Initial Notes" or Letters, inter-doctor communication, nor in the modality of the recording of any kind of note. Conclusions: After the implementation of open notes, progress notes and A&P sections became both longer and easier to read. This suggests clinician documenters may be responding to the perceived pressures of a transparent medical records environment.